2022
DOI: 10.1017/s0047279421001070
|View full text |Cite
|
Sign up to set email alerts
|

Conditional Solidarity - Attitudes Towards Support for Others During the 2020 COVID-19 Pandemic

Abstract: The COVID-19 pandemic presents a unique opportunity to study how humans allocate scarce resources in times of hardship. We study public preferences regarding who should get access to government aid for the self-employed, a bed in the intensive care unit, and permission to cross the border using original conjoint survey experiments administered to an incentivised online panel in Switzerland during the first and second waves of the pandemic in 2020. We find that across the three areas, even in extraordinary circ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…While we consider our results indicate respondents’ appreciation of the positive externality of healthcare and educational workers, we admit that other interpretations are possible. Humans are inclined to heuristically judge deservingness by simplified signals of reciprocity to mutually help by a lighter cognitive load, which is referred to as the “deservingness heuristic” ( Gandenberger et al, 2022 ; Petersen, 2012 ; van Oorschot, 2000 ). Healthcare, educational, and childcare workers’ jobs are supportive of others.…”
Section: Discussionmentioning
confidence: 99%
“…While we consider our results indicate respondents’ appreciation of the positive externality of healthcare and educational workers, we admit that other interpretations are possible. Humans are inclined to heuristically judge deservingness by simplified signals of reciprocity to mutually help by a lighter cognitive load, which is referred to as the “deservingness heuristic” ( Gandenberger et al, 2022 ; Petersen, 2012 ; van Oorschot, 2000 ). Healthcare, educational, and childcare workers’ jobs are supportive of others.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that frontline workers perceived only slightly higher infection risks points to the benefits of building trust in public health systems. Government-led gestures of goodwill and national gratitude also play an important part considering the harassment and aggression that some of these workers may face in the course of their duties to enforce safe distancing rules (Hammonds et al, 2020), and are likely to receive public support given their crucial contributions to the community (Gandenberger et al 2022).…”
Section: Limitations and Directions For Future Researchmentioning
confidence: 99%
“…Holt et al, 2014). Moreover, a related study investigated the solidarity during the pandemic and found that people who did not follow a doctor’s recommendation (Gandenberger et al, 2023), exhibited unhealthy lifestyles, and did not comply with COVID-19-related measures (Reeskens et al, 2021; Schaeffer and Haderup Larsen, 2023) were seen as less deserving of help. To sum up, the willingness to help should be lower if alcohol is ordered, as altruistic behaviour aims at increasing someone else’s welfare.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Recent research has revealed healthcare chauvinism during the pandemic with foreign citizens in Germany being seen as less deserving of intensive care (Gandenberger et al, 2023; Helbling et al, 2022) and individuals having resided in Denmark only shortly being seen as less eligible for hospitalization (Haderup Larsen and Schaeffer, 2021) and vaccination (Schaeffer and Haderup Larsen, 2023).…”
Section: Theoretical Frameworkmentioning
confidence: 99%